ANALISIS TOTAL PREVENTIVE MAINTANANCE PADA MESIN DRILLING KOCH DI PT. XYZ - Rahmadi, Muhamad; Zetli, Sri (Computer Science and Industrial Engineering, 2022)
PT XYZ is a company engaged in ship construction and ship repair. In the field of ship construction this company uses Koch drilling machines in the production process of furniture and other supporting goods on board. Continuous use of the engine cannot be avoided from damage or decreased engine performance. Damage to the machine can reduce the effectiveness in the use of machinery in activities for the production process. Total Productive Maintenance (TPM) is a management principle to increase the productivity and production efficiency of companies by using machines effectively. The object of the study is PT XYZ The purpose of this study was to find out the overall equipment effectivity (OEE) value of drilling machines, as well as to find out the causes and proposed improvements to koch drilling machines. Conclusions that can be taken based on the results of OEE calculations on drilling machines during the period May - October 2022 obtained overall equipment effectiveness (OEE) values ranging between 59.6% to 87.7%. This condition indicates that the ability of the machine in achieving the target and in achieving the effectiveness of the use of machinery or equipment does not achieve the ideal conditions <90%.